Resorcinarene-based cavitands as building blocks for crystal engineering. Issue 31 (16th June 2016) - Pinalli, R.; Dalcanale, E.; Ugozzoli, F.; Massera, C.
Abstract : Since their appearance on the chemistry scene, resorcinarene-based cavitands have been exploited as synthons for the formation of covalent and supramolecular architectures. Being endowed with a pre-organized, π-basic cavity which can be decorated both at the upper and lower rim with a variety of functional groups, they are ideal building blocks for crystal engineering and coordination chemistry. Abstract : Since their first appearance in the chemistry scene thirty years ago, resorcinarene-based cavitands have been recognized to be a highly versatile class of compounds. Endowed with a rigid cavity of molecular dimensions, which can be decorated at the upper and lower rims with a variety of functional groups, they are efficient molecular receptors for chemical sensing, as well as tunable building blocks in the formation of covalent and supramolecular architectures. In this paper, we highlight and discuss "classic" and recent results concerning their chemistry, applications and crystal structure.